The Legal Problems of Ministerial Regulations in the Presidential System of Government - Dillah, Dhea Farah; Nur, Insan Tajali; Hamzah, Herdiansyah (Manunggal Halim Jaya, 2025)
The problem of excessive regulation at the ministerial regulatory level in the presidential system arises because the Minister often exceeds his actual functions. This research aims to analyze the causes of overlapping regulations and authorities that cause legal uncertainty. The results show that excessive regulation is triggered by the unclear type and source of Ministers' authority, limits of authority in the formation of regulations, and the practice of direct delegation that is less controlled.